Vismodegib in patients with advanced basal cell carcinoma: Primary analysis of STEVIE, an international, open-label trial. (November 2017) - Basset-Séguin, N.; Hauschild, A.; Kunstfeld, R.; Grob, J.; Dréno, B.; Mortier, L.; Ascierto, P.A.; Licitra, L.; Dutriaux, C.; Thomas, L.; Meyer, N.; Guillot, B.; et al.
Abstract: Background: The SafeTy Events in VIsmodEgib study (STEVIE, ClinicalTrials.gov, NCT01367665 ), assessed safety and efficacy of vismodegib—a first-in-class Hedgehog pathway inhibitor demonstrating clinical benefit in advanced basal cell carcinoma (BCC)—in a patient population representative of clinical practice. Primary analysis data are presented. Patients and methods: Patients with locally advanced or metastatic BCC received oral vismodegib 150 mg/d until progressive disease, unacceptable toxicity, or withdrawal. Primary objective was safety. Efficacy variables were assessed as secondary end-points. Results: Evaluable adult patients ( N = 1215, 1119 locally advanced; 96 metastatic BCC) from 36 countries were treated; 147 patients (12%) remained on study at time of reporting. Median (range) treatment duration was 8.6 (0–44) months. Most patients (98%) had ≥1 treatment-emergent adverse event (TEAE). The incidence of the most common TEAEs was consistent with reports in previous analyses. No association between creatine phosphokinase (CPK) abnormalities and muscle spasm was observed. Serious TEAEs occurred in 289 patients (23.8%). Exposure ≥12 months did not lead to increased incidence or severity of new TEAEs. The majority of the most common TEAEs ongoing at time of treatment discontinuation resolved by 12 months afterwards, regardless of Gorlin syndrome status. Response rates (investigator-assessed) in patients with histologically confirmed measurable baseline disease were 68.5% (95% confidence interval (CI) 65.7–71.3) in patients with locally advanced BCC and 36.9% (95% CI 26.6–48.1) in patients with metastatic BCC. Conclusions: The primary analysis of STEVIE demonstrates that vismodegib is tolerable in typical patients in clinical practice; safety profile is consistent with that in previous reports. Long-term exposure was not associated with worsening severity/frequency of TEAEs. Investigator-assessed response rates showed high rate of tumour control. ClinicalTrials.gov: NCT01367665 . Highlights: Safety consistent with previous experience: TEAEs are tolerable and mostly reversible. No association between CPK abnormalities and muscle spasm. Long-term vismodegib not associated with worsening frequency/severity of new TEAEs. Response rates were 68.5% in locally advanced BCC and 36.9% in metastatic BCC. Patients with Gorlin syndrome responded better to vismodegib.